Analyses of thymocyte commitment to regulatory T cell lineage in thymus of healthy subjects and patients with 22q11.2 deletion syndrome - Borna, Simon; Dejene, Beruh; Lakshmanan, Uma; Schulze, Janika; Weinberg, Kenneth; Bacchetta, Rosa (Frontiers in Immunology, 2023)
The Chromosome 22q11.2 deletion syndrome (22q11.2DS) results in an inborn error of immunity due to defective thymic organogenesis. Immunological abnormalities in 22q11.2DS patients are thymic hypoplasia, reduced output of T lymphocytes by the thymus, immunodeficiency and increased incidence of autoimmunity. While the precise mechanism responsible for increased incidence of autoimmunity is not completely understood, a previous study suggested a defect in regulatory T cells (Treg) cell lineage commitment during T cell development in thymus. Here, we aimed to analyze this defect in more detail. Since Treg development in human is still ill-defined, we first analyzed where Treg lineage commitment occurs. We performed systematic epigenetic analyses of the Treg specific demethylation region (TSDR) of the FOXP3 gene in sorted thymocytes at different developmental stages. We defined CD3+CD4+CD8+ FOXP3+CD25+ as the T cell developmental stage in human where TSDR demethylation first occurs. Using this knowledge, we analyzed the intrathymic defect in Treg development in 22q11.2DS patients by combination of TSDR, CD3, CD4, CD8 locus epigenetics and multicolor flow cytometry. Our data showed no significant differences in Treg cell frequencies nor in their basic phenotype. Collectively, these data suggest that although 22q11.2DS patients present with reduced thymic size and T cell output, the frequencies and the phenotype of Treg cell at each developmental stage are surprisingly well preserved.